2020
DOI: 10.1002/ece3.6352
|View full text |Cite
|
Sign up to set email alerts
|

A high‐throughput method to quantify feeding rates in aquatic organisms: A case study with Daphnia

Abstract: Food ingestion is one of the most basic features of all organisms. However, obtaining precise—and high‐throughput—estimates of feeding rates remains challenging, particularly for small, aquatic herbivores such as zooplankton, snails, and tadpoles. These animals typically consume low volumes of food that are time‐consuming to accurately measure. We extend a standard high‐throughput fluorometry technique, which uses a microplate reader and 96‐well plates, as a practical tool for studies in ecology, evolution, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Individuals fed for 3 h, after which they were moved to a new well plate for the next feeding rate assay. At the end of each 3-h assay, we measured fluorescence on a plate reader (Tecan, Maennedorf, Switzerland), following Hite et al, 2020, to compare the relative quantities of chlorophyll- a in wells with D. dentifera to control wells that did not contain D. dentifera . We calculated individual feeding rates as:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals fed for 3 h, after which they were moved to a new well plate for the next feeding rate assay. At the end of each 3-h assay, we measured fluorescence on a plate reader (Tecan, Maennedorf, Switzerland), following Hite et al, 2020, to compare the relative quantities of chlorophyll- a in wells with D. dentifera to control wells that did not contain D. dentifera . We calculated individual feeding rates as:…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have indicated that Daphnia have core clock genes and circadian expression of melatonin, immune, and sensory genes (Cellier-Michel et al, 2003; Bentkowski et al, 2010; Bernatowicz et al, 2016; Schwarzenberger and Wacker, 2015; Schwarzenberger et al, 2020, 2021). Daphnia are a model system for studying circadian rhythms in feeding behavior because they reproduce clonally, making individuals genetically identical, and quantifying individual feeding rates is relatively simple (Hite et al, 2020). In their natural habitat, they experience many daily fluctuations that could be used as environmental stimuli for entraining a circadian rhythm.…”
mentioning
confidence: 99%
“…Individuals fed for six hours, after which they were moved to a new vial with fresh COMBO and their body size was measured. We measured algal fluorescence on a plate reader (Tecan, Maennedorf, Switzerland) following Hite et al 2020, to compare the relative quantities of chlorophyll- a in wells with animals to control wells that did not contain animals [ 14 ]. We calculated individual feeding rates as: where F control is the average of fluorescence of control wells, F Daphnia is the fluorescence of an animal well, v is the volume of COMBO and algae in ml, and t is the time individuals fed in hours [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Daphnia are dominant herbivores and serve as keystone species by linking primary producers with secondary consumers in freshwater systems [ 7 ]. Daphnia are an ideal system for addressing if and how feeding behavior and microbial composition are linked because (1) they have a relatively simple microbiome, which has been characterized in multiple species [ 8 , 9 ], (2) they have core clock genes and show circadian expression of feeding behavior, immune, and sensory genes [ 10 13 ], and (3) quantifying individual feeding behavior is straightforward [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Daphnia are dominant herbivores and serve as keystone species by linking primary producers with secondary consumers in freshwater systems [7]. Daphnia are an ideal system for addressing if and how feeding behavior and microbial composition are linked because (1) they have a relatively simple microbiome, which has been characterized in multiple species [8,9], (2) they have core clock genes and show circadian expression of feeding behavior, immune, and sensory genes [10][11][12][13], and (3) quantifying individual feeding behavior is straightforward [14].…”
Section: Introductionmentioning
confidence: 99%